Historical occurrence of Atlantic sturgeon, Acipenser oxyrinchus Mitchill, 1815, in the tributaries of the Vistula River in Poland - Cios Stanisław (Fisheries & Aquatic Life)
All known historical accounts of the occurrence of Atlantic sturgeon (Acipenser oxyrinchus Mitchill) in the tributaries of the Vistula River are presented and analyzed. Sturgeon occurred in most large, medium, and small Vistula tributaries and in the upper reaches of the Vistula River in Silesia. The fish either migrated or strayed there rarely and irregularly, usually as single specimens and mainly during high waters. The data available do not provide evidence that sturgeon spawned successfully in any of the tributaries. In particular, the data do not support the commonly held view that Drwęca was the most important spawning river after 1918, which is the basis of the ongoing sturgeon reintroduction program.